THE EFFECT OF BIOLOGICAL SEX AND THE GLUCOCORTICOID AXIS ON MUSCLE WASTING, RECOVERY AND THE RESPONSE TO EXERCISE IN ACUTE LUNG INJURED MICE - Belfield, Lanazha (Wake Forest University, 2022)
Patients with acute lung injuries, such as severe pneumonia and Acute Respiratory Distress Syndrome (ARDS), develop profound muscle wasting. Muscle wasting involves the loss of muscle mass and function, limiting the ability to recover. The Discovery of mechanisms driving muscle wasting in lung injured patients may lead to new therapeutic approaches. Our lab uses a murine model of Acute Lung Injury (ALI) via lipopolysaccharides instillation into the lung to study the relationship between lung injury and muscle wasting. We have previously shown that muscle atrophy in ALI mice is driven by activation of Muscle Ring Finger-1 (MuRF1), an E3 ubiquitin ligase that targets contractile proteins for proteasomal degradation, leading to weakness. These ALI mice were partially rescued by applying 2 days of moderate-intensity exercise following lung injury (ALI +Ex mice), though the mechanisms underlying this response are incompletely understood. The focus of this project is to 1) understand risk factors for the development of muscle wasting and recovery in ALI mice and 2) understand the upstream events regulating MuRF1 in ALI mice and the response to exercise, and 3) to evaluate time and intensity based thresholds regulating the response to exercise.Some clinical studies have suggested sex-based differences in muscle wasting or recovery in lung-injured patients. To explore this, we studied the role of biological sex on ALI-induced muscle wasting. Overall, we found that male and female mice have similar lung injury and muscle wasting profiles. However, we observed a faster body weight recovery in female mice than in male mice. These data suggests sex-based differences in body weight may stem from a “non-muscle” compartment. Our findings suggest that both male and female mice should be used in this model. Next, we explored the role of the GC stress response on muscle wasting in this model. The promoter of MuRF1 contains a glucocorticoid response element, subjecting it to transcriptional regulation by the glucocorticoid receptor (GR). To study this, we characterized the endogenous stress glucocorticoid response in ALI and ALI +EX mice and evaluated the role of the pharmacologic blockade of GR in these models. We find that ALI mice exhibit a systemic GC stress response and that the GR plays a central role in regulating the response to exercise in ALI mice. Next, we investigated time- and intensity-based thresholds for the exercise response in ALI mice. We found that durations as low as 5 minutes with low intensities (4 m/min) reduced MuRF1 transcription and mitigated type 2 myofiber atrophy. These data suggest that low levels of movement, rather than exercise per se, may be sufficient for silencing MuRF1-mediated atrophy in this model. These data expanded the understanding of the relationship between lung injury and muscle wasting in ALI mice and established new concepts for understanding muscle wasting in critically ill humans.